The impact of real earnings management and ESG to stock price crash risk evidence in Indonesia Stock Exchange - Rahmawanti, Tamara; Suk, Kim Sung (Institute of Computer Science (IOCS), 2023)
The “practice of real earnings management (REM) can increases the stock price crash risk cause information spreads rapidly. However there is hope when a company has a good ESG score, the stock price crash risk can reduce. The study will examine stock price crash risk with hypothesis real earnings management has positive relation and ESG has negative relation with stock price crash risk. Utilizing secondary data, the research comprises a sample of 39 companies with 159 observations, using unbalanced panel data with a fixed-effect model regression choosed. This study research found a positive relationship between“REM”and stock price crash risk and negatife relationship between ESG score using dummy year for crisis Covid-19 era and stock price crash risk. During the Covid-19 period, investors demonstrate a more cautious approach to investment selection, displaying a tendency to opt for companies possessing higher ESG scores, aiming to mitigate the peril of declining stock values